Evaluación del control interno en la dirección de Talento Humano del Gobierno Autónomo Descentralizado Municipal del cantón Chone periodo 2017-2018 - Zambrano Álvarez, Edy Javier (2021)
The purpose of the research was based of internal control in the Direction of Human Talent of the GAD Municipal of the Canton Chone. Its purpose is to verify if the processes used in the department are correct and established in the regulations applied by law for public entities, the study aims to evaluate the control activities with the respective findings and results to implement a strategic plan that contributes to a correct management of the system to solve the problem. In its first phase for the evaluation of the variables, an interview was conducted with the head in charge of the study area to gather information on the processes and procedures of the institution, to keep in mind the institutional procedure with the internal regulations for public institutions and the observation to detail these activities, Based on the instruments carried out, it was possible to know the results of the deficit to the applied control of the people involved in said area, mainly due to the few scarce resources and poorly qualified and trained human resources, he deficiencies discovered give as a conclusion the little work commitment that its employees have, harming the institution and the citizens, for this reason immediate corrections are required for their improvement.